Creating chimeras: Embryonic stem cells incorporated - Pascottini, Osvaldo Bogado (2018)
Gene modification within the murine genome has become a powerful and invaluable tool to investigate development. One example of the utility of such technology is providing a method by which researchers can follow cells throughout development via the introduced genetic modifications.